2016
DOI: 10.1016/j.bbmt.2015.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-Host Disease after HLA-Matched Sibling Bone Marrow or Peripheral Blood Stem Cell Transplantation: Comparison of North American Caucasian and Japanese Populations

Abstract: The risk of acute graft-versus-host disease (GVHD) after HLA-matched sibling bone marrow (BM) transplantation is lower in Japanese than in Caucasian patients. However, race may have differential effect on GVHD dependent on the graft source. North American Caucasian and Japanese patients receiving their first allogeneic BM or peripheral blood stem cell (PBSC) transplantations from an HLA-matched sibling for leukemia were eligible. BM was used in 13% and 53% of Caucasian and Japanese patients, respectively. In m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 26 publications
(27 reference statements)
4
18
0
Order By: Relevance
“…14 These differences may reflect the lower incidence of severe GvHD in the Japanese population derived from genetic homogeneity than in the Caucasian population, 15 suggesting the importance of calculating benchmark rates for GRFS in patients of different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…14 These differences may reflect the lower incidence of severe GvHD in the Japanese population derived from genetic homogeneity than in the Caucasian population, 15 suggesting the importance of calculating benchmark rates for GRFS in patients of different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…First, the risk of GVHD might differ among ethnicities and races. Asian populations were reported to have a lower risk of GVHD compared to Caucasian populations [12]. A Korean study showed that 2.5 mg/kg of ATG-T effectively reduced the incidence of GVHD [13], and our previous study showed that low-dose ATG was associated with a lower risk of chronic GVHD [4].…”
mentioning
confidence: 70%
“…Several studies have reported that the systemic administration of folinic acid, which is routinely used to mitigate MTX toxicities, potentially reduces the incidence of severe oral mucositis after HSCT [25][26][27]. The incidence of GVHD in Japanese patients is lower than that in Caucasians [28,29], possibly due to the more homogenous genetic background of the Japanese population [30]. In many Japanese institutes, day +11 MTX is usually omitted in HLA-matched transplantation from a sibling donor [31,32], whereas four doses are standard in Western countries [15].…”
Section: Discussionmentioning
confidence: 99%